Analisis Penentuan Sektor Basis dan Sektor Unggulan Sebagai Penggerak Pertumbuhan dan Pembangunan Ekonomi Kabupaten Tanah Laut - Anshori, Muhammad Fahreza; Fahrati, Eny (PPJP ULM, 2025)
This study aims to (1) determine which sectors are at the forefront of the economy and base sectors; and (2) to find out which economic sectors have the potential to become base sectors. This research uses Location Quotient (LQ), Dynamic Location Quotient (DLQ), Growth Ratio Model (MRP), Klassen Typology, and Overlay analysis techniques. Using GDP data on constant prices in 2010 according to business fields for 2018-2022. The results showed that the agriculture, forestry, and fisheries sectors, mining and quarrying sectors, large trade and retail sectors are the base sectors. The sector of mining and quarrying holds a prominent position in Tanah Laut Regency because it has a positive contribution and growth. Meanwhile, sectors that have the potential to become base sectors in the future are the manufacturing industry sector, electricity and gas procurement, construction, transportation and warehousing, financial and insurance services, corporate services, land government administration and compulsory social security.